Phylogenetic analysis of Aceh cattle breed of Indonesia through mitochondrial D-Loop region - Sari, E.M.; Han Jianlin; Noor, R.R.; Sumantri, C.; Margawati, E.T. (Springer, 2016)
The objective of this research was to find the basic data on genetic diversity of mtDNA D-Loop in Aceh cattle and its association with Bhutanese, Chinese, and Indian cattle. There were sixty samples of DNA which had been sequenced; i.e. Banda Aceh (11), Saree (20), and Indrapuri (29). To the best of our knowledge this is the first published data on the complete mitochondrial D-Loop sequence of Aceh cattle. Results show that Aceh cattle have the closest relationship to Bos indicus and have been influenced by Bos taurus. The closest genetic ranges among Aceh cattle, Bhutanese, Chinese, Indian and Zebu were Aceh–Zebu (0.0138), Aceh–Bhutanese (0.0156), Aceh–Chinese (0.0190) and Aceh–Indian (0.0193). D-Loop mtDNA analyses showed that there were 27 haplotypes in which twenty-one samples spread in haplotype 1, two samples were in haplotype 2, and the other four haplotypes had various samples in the range of three to seventeen samples. One sample of Aceh cattle from Saree has a closest maternal genetic with B. taurus. One of the four mutations among the star-shaped clusters on median joining network was a new specific haploid-group in Aceh cattle. From this finding it could be assumed that Aceh cattle form a specific haplotype and it can be conclude that Aceh cattle are animal genetic resources from Aceh in Sumatera Island that have to be preserved.